SPECTRUM OF BACTERIAL CULTURE AND DRUG SENSITIVITY VS RESISTANCE IN UNCOMPLICATED URINARY TRACT INFECTION - Jadoon, Shakeel Ahmed; Ahmed, Ashfaq; Irshad, Romana (Journal of Ayub Medical College Abbottabad, 2018)
Background: The growing antibiotic resistance against uropathogens has made its treatment a challenge for the physicians. This study was conducted to know the spectrum of bacteria responsible for urinary tract infection and their susceptibility and resistance to available antibiotics. Methods: This hospital based cross-sectional study was carried out from May to October 2017. All patients presenting with urinary tract infection signs and symptoms and were included in the study. A sample of 168 patients of both gender and age were recruited for the study using convenient sampling technique. Antimicrobial isolation and differentiation was determined by using Cystine-lactose Electrolyte Deficient (CLED) Agar. Susceptibility and resistance to 30 available antibiotics were determined. Data was collected on the pre-designed proforma. SPSS version 16 was used for data entry and analysis. Results: There were 62 (36.9%) males and 106 (63.1%) females. Mean age of the male patients was 55.34±21.33 years whereas the mean age of the female patients was 45.8±22.07 years and the difference was statistically significant (p=0.007). Gram negative bacteria were isolated from 141 (83.9%) of the cases. Gender wise distribution of Gram negative and positive strains was found statistically significant (p=0.032). E. coli was the commonest bacterium found in 70.8% of cases. It was sensitive to only seven (23%) antibiotics in over 80% of the cases. E. faecalis, K. pneumoniae, P. aeruginosa and S. faecalis were susceptible to 13%, 26.7%, 40% and 23% of antibiotics respectively in over 60% of the cases. 90% of the cultured pathogens were susceptible to Nitrofurantoin in over 80% of the cases. Among cultured pathogens, 70% showed susceptibility to Imipenem, Meropenem, Amikacin, Doxycycline, Fosfomycin and Cefoperazone/Sulbactam in over 60% of the cases. Conclusion: UTI is more common in women as compared men. E. coli, E. faecalis, K. pneumoniae and P. aeruginosa are the major pathogens responsible for UTI in this part of the country and in over 80% of the cases are still sensitive to Nitrofurantoin. Keywords: Urinary tract infection; Gram positive and negative uropathogens; antibiotic susceptibility